1969
DOI: 10.1111/j.1365-2141.1969.tb05660.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Erythroblastic Multinuclearity Associated with a Positive Acidified‐Serum Test: a Type of Congenital Dyserythropoietic Anaemia

Abstract: Summary. In five patients (including two sisters) an unusual anaemia was characterized by erythroblastic multinuclearity, ineffective erythropoiesis and a positive acidified‐serum test. Unlike PNH, the sugar‐water test was always negative in these patients. The lysis of their cells by acidified normal sera indicated their abnormal sensitivity to an agglutinating and complement‐binding antibody present in some normal subjects. The patients cells gave high agglutination scores with anti‐i, and were unusually sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(107 citation statements)
references
References 18 publications
4
103
0
Order By: Relevance
“…CDA II is associated with well-defined cellular and ultrastructural features including binucleated or multinucleated late precursors, flat vesicles of variable length, and a double membrane beneath the cytoplasmic membrane. 3,4 The principal biochemical feature is the hypoglycosylation of several proteins, such as transferrin and band 3. 5,6 Much research has been devoted to enzymes involved in glycan synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…CDA II is associated with well-defined cellular and ultrastructural features including binucleated or multinucleated late precursors, flat vesicles of variable length, and a double membrane beneath the cytoplasmic membrane. 3,4 The principal biochemical feature is the hypoglycosylation of several proteins, such as transferrin and band 3. 5,6 Much research has been devoted to enzymes involved in glycan synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most widely documented subtype of CDA, with approximately 367 cases reported in the literature, predominantly in European populations [15]. The term HEMPAS derives from observations by Crookston et al that the red blood cells from CDA II patients demonstrated susceptibility to lysis in ABO-compatible normal sera in the acidified serum lysis test (HAM's test) [16]. CDA II is an autosomal recessive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…According to previously proposed classification schemes [24,25], confirmation of CDA II includes sodium dodecyl sulfate polyacrylamide gel electrophoresis for erythrocyte band 3 protein [26], acidified serum lysis testing (HAM's test) [16], electron microscopy to demonstrate the presence of a double membrane adjacent the cell membrane in mature red blood cells [27], or assessment of mutation status of the recently recognized SEC3B gene [12]. These specialized tests, however, are not available in most clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocytes of patients with CDA type II are lysed in the acidifi ed serum lysis test(Ham's Test) but not the patient's serum. Consequently, CDA type-II is also described as hereditary multinuclearity with a positive acidifi ed serum lysis test(HEMPAS) [11]. A positive Ham's test is also seen in paroxysmal nocturnal hemoglobinuria the difference being that here it is positive even in the patient's own serum.…”
Section: Discussionmentioning
confidence: 99%